IMPLICATIONS OF TRANSITIONAL JUSTICE IN SYRIA: EXAMINATION AND ANALYSIS - Asal Haji Rezaei (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The Syrian crisis began in 2011, following popular protests over the Syrian government’s performance, fueled by the suppression of the protests and the confrontation with the will of the society and with the intervention of foreign agents and governments; It became a scene of confrontation between the state and the nation, and then this crisis took on the color of armed conflict. One of the proposed mechanisms for overcoming the humanitarian crisis caused by the violation of international humanitarian law is transitional justice. Transitional justice includes a set of judicial and non-judicial mechanisms to compensate for the post-collapse human rights violations of a regime. The present study analyzes the effects of transitional justice in the Syrian crisis with an analytical-explanatory method and finally, considering the nature of the Syrian crisis, considers transitional justice as the only way to prevent any human danger in the future, except through the International Court of Justice. It will not be achieved through the establishment of a special branch of the ICC or the establishment of a special tribunal by the United Nations; In this regard, the Commission of Inquiry of the Syrian Arab Republic has provided the ground for the realization of transitional justice and the reform of political structures to restore the rule of law.